Valourizing agricultural farm waste with bioinoculants for plant growth promotion and disease management - Manoranjitham, S K; Siva, M; Malathi, P; Geethalakshmi, V; Sendhilvel, V; Jensipershiya, S (Plant Science Today, 2025)
Soilborne pathogens such as Fusarium spp., Pythium spp., Phytophthora spp., Verticillium spp. causes significant yield loss to various agricultural and horticultural crops. These diseases are difficult to control by chemicals which are harmful to environment and crop health. On the other hand, continuous usage of pesticides leads to the development of pesticides resistance by the pathogens. Valourizing the farm waste by microbial bioinoculants is an alternative and promising approach for controlling soilborne diseases. Farm waste releases bioactive compounds with antifungal and antibacterial properties. Farm waste utilization reduces pesticide dependence by enriching soil, enhancing microbial diversity and promotes sustainable agriculture. Microbial bioinoculants serve as alternatives to synthetic pesticides for the management of plant pathogens. Beneficial microbes like nitrogen-fixing bacteria, phosphate-solubilizing microbes and biocontrol agents play a crucial role in strengthening the plant immunity against pathogens. These beneficial organisms not only improve soil biodiversity but also ensure better plant growth and development. This review focuses on the enrichment of agricultural farm wastes such as fruits and vegetable waste, coir pith, farm yard manure, biochar and chicken manure with bioinoculants for soil borne disease management. Harnessing microbial bioinoculants for farm waste valorization presents a promising pathway toward sustainable agriculture, ensuring environmental protection and long-term soil health.